Branding Strategies as a Tool for Competitive Growth in Local Pharmaceuticals: Strategi Branding sebagai Alat untuk Pertumbuhan Kompetitif di Industri Farmasi Lokal - Latifovich, Khasanov Sokhib (Academia Open, 2025)
General Background: The pharmaceutical industry plays a pivotal role in national healthcare and economic security, especially under increasing global competition and consumer demand. Specific Background: In Uzbekistan, recent state reforms have driven growth in the local pharmaceutical sector, yet many enterprises lack strategic branding, limiting their market competitiveness. Knowledge Gap: Despite global recognition of branding’s impact, local studies inadequately address its strategic, psychological, and institutional dimensions, often reducing it to superficial elements like logos or product names. Aims: This study aims to analyze the role of branding strategies in shaping a competitive environment among Uzbek pharmaceutical enterprises and to propose context-specific solutions for brand development. Results: The analysis reveals that domestic products occupy 37% of the market by volume but only 13% by value, highlighting a branding deficit. Strategic branding can enhance consumer trust, differentiate products, and increase export readiness. Novelty: The study integrates multidisciplinary branding theories with local market analysis, offering practical, evidence-based branding recommendations tailored to Uzbekistan’s pharmaceutical sector. Implications: Effective branding strategies can serve as tools for sustainable competitiveness, transforming local pharmaceutical brands into assets that foster customer loyalty, attract investment, and bolster national economic resilience. Highlights: Strategic Branding Is Essential Branding is not just logos—it builds consumer trust, emotional connection, and long-term market positioning for local pharmaceutical firms. Local Brands Are Underdeveloped Despite making up 37% of consumption, most Uzbek pharmaceutical companies lack a full branding platform and remain focused only on product names and packaging. Branding Boosts Export and Investment A strong brand image increases not just domestic loyalty but also international market access and investor appeal. Keywords: Branding Strategy, Pharmaceutical Industry, Competitive Advantage, Consumer Trust, Uzbekistan